Assisting Functional Assignment for Hypothetical Heamophilus influenzae Gene Products through Structural Genomics - Gilliland, G.L.; Teplyakov, A.; Obmolova, G.; Tordova, M.; Thanki, N.; Ladner, J.; Herzberg, O.; Lim, K.; Zhang, H.; Huang, K.; Li, Z.; Tempczyk, A.; et al. (Current Drug Targets - Infectious Disorders, 2002)
The three-dimensional structures of Haemophilus influenzae proteins whose biological functions are unknown are being determined as part of a structural genomics project to ask whether structural information can assist in assigning the functions of proteins. The structures of the hypothetical proteins are being used to guide further studies and narrow the field of such studies for ultimately determining protein function. An outline of the structural genomics methodological approach is provided along with summaries of a number of completed and in progress crystallographic and NMR structure determinations. With more than twenty-five structures determined at this point and with many more in various stages of completion, the results are encouraging in that some level of functional understanding can be deduced from experimentally solved structures. In addition to aiding in functional assignment, this effort is identifying a number of possible new targets for drug development.
Keywords: Cloning